Basic fibroblast growth factor blockade enhances lung cancer cell invasion by activating the AKT/MMP‐2/VEGF pathway. Issue 1 (8th August 2019) - Wang, Zhiyong; Xu, Huan; Zhang, Junai; Jin, Hua; Wei, Pei
Abstract: Basic fibroblast growth factor (bFGF) can stimulate cancer cell growth and invasion; however, the influence of bFGF blockade remains unclear. Therefore, we aimed to explore the effects of bFGF blockade on the growth and invasion in A549 (high bFGF expression) and H2122 (low bFGF expression) lung cancer cells. We found that the blocking of bFGF by a neutralizing monoclonal antibody suppressed the growth of A549 cells but not of H2122 cells, as well as strongly induced the invasiveness of A549 cancer cells. Furthermore, bFGF blockade activated the AKT pathway and enhanced the expression levels of matrix metalloproteinase (MMP)‐2 and vascular endothelial growth factor (VEGF) in A549 cells. These responses could be reversed by treatment with AKT inhibitor and siMMP‐2, thus indicating the involvement of the AKT/MMP‐2/VEGF‐positive feedback loop. Finally, we confirmed that the anti‐bFGF‐induced invasion of cancer cells could be rescued by inhibiting the AKT/MMP‐2/VEGF loop. Our results revealed that bFGF blockade suppresses cell growth but promotes cell invasion in lung cancer cells with high bFGF expression levels. Our data further reinforced the importance of the AKT/MMP‐2/VEGF loop in regulating anti‐bFGF‐induced tumour cell invasion and suggested the limitations of the bFGF‐targeting strategy in lung cancer treatment.